Analisis Masalah Perkembangan Kognitif Murid dalam Penerapan Kurikulum Merdeka - Fia Citra Bahrulinnisa; Laelia Nurpratiwiningsih; Moh Toharudin (Peneliti.net, 2023)
The independent curriculum is implemented in class IV with learning methods that adapt to students' cognitive conditions in order to achieve learning outcomes. Some students do not understand the lesson material given by the teacher. An independent curriculum tends to focus more on the cognitive performance of students. Students' cognitive problems, delays in literacy such as not being able to read are often complained about by teachers. Apart from this, it tends to be difficult for students to concentrate on learning and it takes a long time to understand the subject matter and many students experience learning difficulties. Based on the description of the results of initial observations carried out by the researcher, in this research the researcher took the title